O problema do cientificismo - Oliveira, Bruno Camilo de (2018)
It should be admitted the possibility of there being knowledge beyond natural science? This work argues that yes. It studies how scientism – an ideological perspective that natural science, of empirical observational root, is the only possible source of knowledge – can have undesirable implications for science and society. A study of the history of scientism and its frequent confusion with science, for example, is able to show what made contemporary science so persuasive and powerful, but capable of creating obstacles for its own development. Scientism is a theory about the explanatory power of science, and not of science itself. The problem is the limitations that this theory drags on science. Thus, this paper aims to present the reasons by which scientism can and should be refuted. It is presented a study on the general problem of scientism from of confirmation of five specific problems: the confusion between science and scientism; the metaphysical treatment – in the doctrinal sense – given to science said natural; the atheism and the reduction of religion to scientific categories; the exaltation of the technology itself; and the defense of a closed epistemology. It is interesting to consider the implications that these problems can bring, mainly in view of the growing increase of contemporary works with scientism bias. Such works have justified the dogma of scientism mainly based on the success of technological results and on the capacity of science to describe regularities. However, other works have emphasized that these and other characteristics of natural science are not sufficient for the defense of the scientism position, once that, on the one hand, that science is fallible, while on the other it can be extremely plural and interdisciplinary. That way, the present work examines the scientism of other authors to show the fallacy of his arguments. It considers studying definitions presented in other works to support the thesis that natural science is certainly capable of formidable actions, but not sufficient to support the scientism attitude.